20.1k views
2 votes
I need to figure out the easiest way to solve this and apply the method to every problem

I need to figure out the easiest way to solve this and apply the method to every problem-example-1
User Kett
by
6.4k points

1 Answer

0 votes

The function is given as,


f(x_()=-3x^2-7x)

It is asked to find the value of the expression,


f(7)

This can be obtained by replacing 'x' by 7 in the given expression of the function,


f(7)=-3(7)^2-7(7)

Resolve the parenthesis,


\begin{gathered} f(7)=-3(49)-49 \\ f(7)=-147-49 \end{gathered}

Simplify the terms further,


f(7)=-196

Thus, the value of the expression f(7) is obtained as,


=-196

User Kbz
by
5.2k points